PENGGUNAAN VARIASI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MOTIVASI DAN MINAT BELAJAR MATEMATIKA SISWA KELAS XI IPS 3 SMA NEGERI 2 MERAUKE - Dessy Rizki Suryani; Nurindah Lestari (Musamus University, 2019)
Abstract: This Classroom Action Research (CAR) aims to increase motivation and interest in learning mathematics in class XI IPS 3 of SMA Negeri 2 Merauke by using a variety of learning media. The subjects in this study were 30 students of class XI IPS 3, 17 male students and 13 female students. The cycleof CAR uses the Kemmis & Mc Taggart model with stages of planning, implementation, observation, and observation. Pre-cycle data shows that students' motivation and interest in learning mathematics are in the low category. The study was conducted in 2 cycles with 4 meeting for each cycles. Based on the results of student observation activities indicate that student activities have increased in learning process of cycle I and cycle II. The average percentage of student learning activity in the first cycle reached 57%, and increased in the second cycle, amount 83%. Increased percentage of student’s learning activity in cycle I and cycle II by 26%. Student learning motivation in the good category experienced an increase from pre-cycle with a percentage of 37.16%, 62.72% in the first cycle, and 90.12% in the second cycle. Student’s interest in the good category also increased from pre-cycle with a percentage of 35.34%, in the first cycle 58.55%, and in the second cycle increased to 93.55%. Based on the results of this study it can be concluded that by using a variety of learning media can increase motivation and interest in learning mathematics in class XI IPS 3 of SMA Negeri 2 Merauke. With the motivation and interest in learning students towards mathematics, it is expected that students themselves will be able to more easily understand mathematics and mathematics no longer be a frightening subject for students. Keywords: variations in learning media, motivation, interests.